Komisi Kebenaran dan Rekonsiliasi, Permasalahan dan Prospeknya - Lesmana, Tjipta (LAW REVIEW, 2005)
As a nation and state Indonesia is currently in a terribly "bad shape " facing multi-dimension crisis, foremost are economic crisis, judicial crisis and moral crisis. Etnic as well as vertical conflicts are pervasive everywhere. Promoting national unity and reconciliation are absolute prerequiste to address those crisis. Creation of Commission for Truth and Reconciliation as stipulated in Act Number 34/2004 is a positive and important step for crisis management. Implementation of The Commission, however, should be carefully and wisely guided. The Commission is not to punish, bur rather to Â uncover and heal the nation. Those who confessed their crimes truthfully should be granted immunity from prosecution. Ultimately, the goals of Commission is to contribute to end and account for past abuses of authority, to promote national reconciliation and/or bolster a new political order or legitimize new policies. To fulfil its objective it is imperative that the Commission comprise of members whose loyalty to Unity State (NKRI), Pancasila and Constitution is firm, non-pratisan, and has a strong drive to promote the just and prosperous Indonesia in the future.